Use of Terrestrial Laser Scanning for Measurements of Wind Power Stations - Mitka, Bartosz; Klapa, Przemysław; Gniadek, Jacek (Geomatics and Environmental Engineering, 2019)
The continuous development of the technologies used in the construction of wind turbines makes them a promising and widely used source of energy. Wind turbines keep getting bigger, resulting in increases in their production capacity. However, both the wind turbines and their support structures are exposed to huge loads that cause the deformation of the rotor blades, vertical deflection, or vibration of the support structure and rotor blades. In this context, the issue of monitoring the technical condition of the structures of such facilities becomes important, particularly in terms of reliability and the service life of the whole system. This document shows a method of measuring a wind power station using the Leica P40 terrestrial laser scanner. The object of the research was a few-years-old wind turbine located in the village of Kluczewsko (near Włoszczowa). The examined wind turbine is 35 m high measured to the turbine base and has rotor blades that are almost 13 m long. The measurements were performed at two stages: during turbine operation and with the wind turbine at rest. This enabled us to determine the changes in the geometry of the object at dynamic loads during the operation of the plant. Each series of measurements was made from three stations evenly arranged around the entire facility, which allowed for a full recording of the wind turbine geometry as well as of its supporting structure. The measurements taken at rest and during operation of the turbine were recorded on the basis of the same points of reference, which allowed us to obtain data on the same coordinate system. The measurements were used to determine the deflection of the turbine support from the vertical axis at rest and the change of deflection under wind pressure during the turbine´s operation. The vibration amplitude of the turbine´s support during operation was also determined. In addition, an attempt was made to determine any changes in the geometry of the rotor blades under wind pressure. The obtained results are presented in a tabular and graphical manner.